Non-Traumatic Subarachnoid Hemorrhage with Brain Abscess due to Eisenmenger Syndrome: A Rare Case Report - Muhammad Ikhlas Muttaqin Aditiarman; Dhesty Fadhilah Faatin; Ni Nyoman Ayu Susilawati (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Non-traumatic subarachnoid hemorrhage in patients with congenital heart disease, such as Eisenmenger syndrome, may involve multiple organs and carries a risk of cerebral abscess due to multiorgan mechanisms. Case: A 20-year-old male with untreated congenital heart disease since childhood was admitted with severe headache, neck stiffness, projectile vomiting, fatigue, lip curling, slurred speech, and stroke-like symptoms. Neurological deficits included right-dominant tetraparesis, accompanied by cyanosis and clubbing of fingers. CT scan revealed a subarachnoid hemorrhage extending into the perimesencephalic cistern with a thick-walled hypodense lesion, suspected to be a brain abscess. Laboratory findings revealed secondary erythrocytosis, characterized by elevated hematocrit and erythrocyte levels. Discussion: In this case, the subarachnoid hemorrhage was non-traumatic and perimesencephalic, likely caused by a mycotic aneurysm associated with Eisenmenger syndrome. The brain is a frequent target of septic emboli linked to mycotic aneurysms that trigger hemorrhage. Hemodynamic instability contributes to arterial endothelial degeneration, while hyperviscosity from congenital heart disease and septic embolism facilitates aneurysm formation. Rupture of such aneurysms leads to a sudden rise in intracranial pressure, worsening neurological outcomes. Conclusion: Subarachnoid hemorrhage in Eisenmenger syndrome is strongly associated with mycotic aneurysms from septic emboli, which may progress to cerebral abscess due to diffuse hypoxia from impaired cardiac output. Early diagnostic evaluation is crucial to establish the etiology, and heightened vigilance is needed in Eisenmenger cases, given the elevated risk of subarachnoid hemorrhage through septic emboli and aneurysm rupture.